O conceito de observabilidade segundo Bas Van Fraassen e a sua relevância para o empirismo construtivo - Alessio Gava (2010)
The aim of this work is to analyze and present Bas van Fraassens concept of observability and its relevance for the philosophical stance known as Constructive Empiricism. We will show how the issue of distinguishing between the observable and the unobservable part of the world plays a crucial role in the discussion about the scientific enterprise, regardless of the conflicting philosophical positions. The observable / unobservable dichotomy is fundamental for Logical Empiricism, but not less important for its adversary, Scientific Realism. We will show that a new anti-realist stance, van Fraassens Constructive Empiricism, appearing to be an intermediate position, is based on this distinction. The central role of the concept of observability in the present debate in Philosophy of Science will also be demonstrated in this work.